Project Selection in Construction Industry by MCDM Method and Machine Learning Approach - Hu Cheni, Lee; Zhing Tai, Lixiau (International journal of industrial engineering and operational research, 2023)
Project selection in the construction industry plays a crucial role in ensuring the success and profitability of construction projects. Various factors, such as cost, time, quality, and resources, need to be carefully evaluated during the project selection process. This paper presents a comprehensive study on project selection in the construction industry using the Multiple Criteria Decision Making (MCDM) method combined with a machine learning approach. The objective is to provide a systematic and objective framework for project selection that considers diverse criteria and enhances decision-making accuracy in the construction industry.